Potential and Challenges in Implementing the Merdeka Belajar Curriculum at schools in Nias Utara - Juardiman Putra Gea (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article explores the potential and challenges associated with implementing the Merdeka Belajar Curriculum in Indonesia. The method used in this article is a quantitative method by interviewing several teachers at the school. The curriculum is anticipated to enhance education quality by offering flexibility for teachers, enabling students to pursue learning based on their interests, boosting student motivation, and fostering the development of 21st-century skills. However, the article highlights several challenges, including teacher readiness, availability of facilities, mindset change, and the need for effective evaluation. It underscores the crucial requirement for support from the government, schools, teachers, students, and parents to effectively address these challenges and successfully implement the curriculum.